Pengaruh Pre-roasting Terhadap Kinetika Leaching Fe dari Laterite Tipe Limonite - Gyan Prameswara (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2024)
Extraction of valuable metals from laterite is intensified. The scarcity of sulfide sources containing high Ni and the use of pyrometallurgical processes with high capital costs are important reasons to initiate extraction of valuable metals from oxide minerals such as laterite and hydrometallurgical processes such as leaching. In this study, the effect of pre-roasting of limonite type laterite on Fe leaching kinetics parameters was observed. Roasting was carried out at 280 °C and 610 °C to transform the geotite phase into hematite and dehydroxylate Mg-Si associated minerals. Roasting was carried out for 4 hours in a muffle furnace. Non-roasted and roasted ore were then leached at a temperature range of 30-90 °C at a time variation of 0 to 240 minutes using sulfuric acid at a concentration of 2M, S/L ratio of 10 g/100 mL, and rotating speed of 200 rpm. Roasted ore (280 °C) showed better leaching performance than non-roasted ore while increasing the roasting temperature to 610 °C did not provide a significant increase in Fe recovery. Kinetic parameters such as activation energy (EA) and frequency factor were also reduced by using roasted ore. An EA value of 31.66 kJ/mol was obtained in the leaching process using 280 °C roasted ore. The leaching process is confirmed to be controlled by diffusion through the product layer with the following kinetic equation kt=31.59 exp (-31.66/(RT))t=1-2/3X-(1-X)^(2/3).